2010
DOI: 10.1007/s00449-010-0469-8
|View full text |Cite
|
Sign up to set email alerts
|

Mathematical modeling of the integrated process of mercury bioremediation in the industrial bioreactor

Abstract: The mathematical model of the integrated process of mercury contaminated wastewater bioremediation in a fixed-bed industrial bioreactor is presented. An activated carbon packing in the bioreactor plays the role of an adsorbent for ionic mercury and at the same time of a carrier material for immobilization of mercury-reducing bacteria. The model includes three basic stages of the bioremediation process: mass transfer in the liquid phase, adsorption of mercury onto activated carbon and ionic mercury bioreduction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 5 publications
1
27
0
Order By: Relevance
“…Most studies on the reduction kinetics of heavy metals such as mercury [ 54 ], arsenate [ 55 ], and chromate [ 56 ] reported a Haldane-type inhibition by the substrate metal ions. However, molybdenum reduction to Mo-blue showed a clear strong inhibition of Mo-blue production rate at high concentration of molybdenum with a calculated critical concentration of molybdenum that completely inhibited Mo-blue production at 108.22 mM.…”
Section: Discussionmentioning
confidence: 99%
“…Most studies on the reduction kinetics of heavy metals such as mercury [ 54 ], arsenate [ 55 ], and chromate [ 56 ] reported a Haldane-type inhibition by the substrate metal ions. However, molybdenum reduction to Mo-blue showed a clear strong inhibition of Mo-blue production rate at high concentration of molybdenum with a calculated critical concentration of molybdenum that completely inhibited Mo-blue production at 108.22 mM.…”
Section: Discussionmentioning
confidence: 99%
“…Kong et al 47 use the modified Gompertz model to model the growth of bacterium in the presence of chromium during the latter's reduction. The Haldane model has been cited for modelling the kinetics of metal-reducing bacterium such as mercury, 53 arsenate 54 and chromate. 55 It is a modification to the Monod model, which in turn was inspired by the Michaelis-Menten enzyme kinetics model.…”
Section: Resultsmentioning
confidence: 99%
“…The reduction kinetics of metal-reducing microbes, nevertheless, is less studied. Currently, almost all the scientific studies on the reduction kinetics of heavy metals, for instance mercury (Głuszcz et al 2011), arsenate (Soda et al 2006) and chromate (Sukumar 2010), reported a Haldane-type inhibition. An investigation on uranium reduction, however, shows Monod kinetics (Truex et al 1997).…”
Section: Introductionmentioning
confidence: 99%